Psychotherapy, symptom outcomes, and role functioning over one year among patients with bipolar disorder. - Miklowitz, D; Otto, M; Wisniewski, SR; Araga, M; Frank, E; Reilly-Harrington, N; Lembke, A; Sachs, G (2006)
OBJECTIVE: Randomized trials indicate that psychosocial interventions effective adjuncts to pharmacotherapy in bipolar disorder (1,2). A one-year naturalistic-prospective design was used to examine the association between psychotherapy use and the symptomatic and functional outcomes of patients with bipolar disorder. METHODS: Patients with bipolar disorder in a depressed phase (N=248) were drawn from the first 1,000 enrollees (November 1999 to April 2002) in the Systematic Treatment Enhancement Program (STEP-BD), a study of patients with bipolar disorder receiving best-practice pharmacotherapy. Patients were seen clinics and interviewed every three months over one year regarding of psychotherapy services, symptoms, and role functioning. Mixed-effects regression models were used to examine whether the amount of psychotherapy the patients received during each three-month interval was associated with symptomatic or psychosocial functioning during the same or a subsequent three-month interval. RESULTS: During the study year, percent of the patients had at least one psychotherapy session. Among patients who began an interval with severe depressive symptoms or low functioning, having more frequent sessions of psychotherapy was associated with less severe mood symptoms and better functioning in the same or a subsequent study interval. In contrast, among patients who began interval with less severe depressive symptoms or higher functioning, fewer psychotherapy sessions were associated with less severe depressive symptoms and greater functioning in the same or a subsequent interval. CONCLUSIONS: Intensive psychotherapy may be most applicable to severely ill patients with bipolar disorder, whereas briefer treatments may be adequate for less severely ill patients.